Virtual Appliances for geospatial data management and processing in the Integrated Land Management System (ILMS) - Schwartze, Christian; Zander, Franciska; Kralisch, Sven; Flügel, Wolfgang-Albert (Acta Agraria Debreceniensis, 2012)
Virtualization is increasingly taking on a key role in various system architectures which follow new platform concepts like Software as a Service (SaaS). This trend addresses more instant and short-term environments and comes with new methods and strategies for the distribution of mainly complex application stacks not only in large IT infrastructures. The paper presents how a so called Virtual Appliance can be set up in order to operate in virtual server environments using hypervisor software like Oracle Virtual-Box. Using the example of two server-side components within the Integrated Land Management System (ILMS), it will be shown that the use of state-of-the-art methods, standardized tools and interfaces on servers enables different aspects of environmental system management, analysis and planning.